Monatomic Co-anchored TiO2 catalyst as well as preparation method and application thereof
Through the preparation method of high-load single-atom Co on TiO2 catalyst, combined with peroxysulfate and photocatalysis, the problems of single-atom loading and stability of the TiO2 catalyst surface are solved, and efficient organic pollutant degradation and economic cost are achieved. reduce.
Patent Information
- Application Number
- CN202411112145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The prior art is difficult to effectively improve the single-atom loading and stability of TiO2 catalyst surface, resulting in low degradation efficiency of organic pollutants and unable to meet environmental protection needs.
Using a single-atom Co-anchored TiO2 catalyst, the thermal reaction of dicarboxylic acid and organic titanium, hydrothermal etching and cobalt-based compound calcination were prepared. Catalysts and are used in conjunction with peroxysulfate for photocatalysis.
It has achieved a 100% degradation rate for persistent organic pollutants such as plasticizers, which has good anti-interference and reusability, and significantly reduced the economic cost of the catalyst.
Smart Images

Figure CN119175098A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic pollutant treatment, and particularly relates to a single-atom Co-anchored TiO2 catalyst and a preparation method and application thereof. Background Art
[0002] Dibutyl phthalate (DBP) is one of the commonly used plasticizers in industrial production. It is cheap and easy to process. Its output and usage are very large. It is very easy to be released into the environment during processing and use. It has the characteristics of light color, small odor, low temperature resistance and difficulty in natural degradation. Due to the excellent stability of phthalate plasticizers, their hydrolysis half-life is very long and there is almost no volatilization loss. However, organisms have an enrichment effect on phthalate plasticizers. Studies have shown that there are obvious residues of this type of compound in aquatic organisms. Phthalate plasticizers cause adverse effects on organisms such as tissue canceration, developmental deformity, reproductive toxicity, and gene mutation. Due to the widespread use of phthalate plasticizers, the presence of DBP can often be detected in water, soil, food and atmosphere.
[0003] With the improvement of national environmental protection control standards and the enhancement of public environmental safety awareness, the technology of treating organic pollutants in water bodies has attracted more and more attention. Studies have shown that photocatalysis and peroxysulfate have a positive synergistic effect on the removal of organic pollutants. Compared with a single treatment method, the method of synergistic treatment is effective and more efficient. There are many existing literature reports that noble metals (Au, Pt, Ag and Pd), transition metals (Cr, Mn, Fe, Co, Ni, Cu and Zn) or lanthanides (La, Nd, Sm, Eu, Gd, Yb or Pr) are used as doping metals to improve the photocatalytic activity of TiO2. However, due to the easy agglomeration of single atoms and the limited surface area of the carrier, the single atoms are unstable on the surface of the carrier and are easy to fall off, and the loading amount of the single atoms is low, and the single atom weight loaded on the surface of the carrier is often no more than 0.3wt%. Because the single atoms loaded on the surface are easy to agglomerate, the catalyst system is unstable, the catalytic activity is low, and the efficiency of catalytic degradation of organic pollutants is low, which cannot meet the needs. How to make the single atoms have a high dispersion on the surface of the carrier, stable attachment, and high loading amount is a difficult point in preparation. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a single-atom Co-anchored TiO2 catalyst and its preparation method and application. The catalyst provided by the present invention has a high Co loading on the surface and can 100% degrade the plasticizer dibutyl phthalate.
[0005] The present invention provides a single-atom Co-anchored TiO2 catalyst, comprising nano-TiO2 and single-atom Co;
[0006] The single atomic Co is dispersed on the surface of the nano-TiO2;
[0007] The loading amount of the single-atom Co is 0.1-1wt%, and the rest is nano-TiO2;
[0008] The nano-TiO2 is donut-shaped, with an outer diameter of 500-700nm, an inner diameter of 50-300nm, and a thickness along the normal direction of the nano-TiO2 of 300-400nm; the specific surface area of the nano-TiO2 is 100-150m 2 / g.
[0009] The present invention also provides a method for preparing the single-atom Co-anchored TiO2 catalyst described in the above technical solution, comprising the following preparation steps:
[0010] The dicarboxylic acid is mixed with the organic titanium and subjected to a thermal reaction to obtain a MIL-125 precursor;
[0011] The MIL-125 precursor is mixed with tannic acid, and subjected to a hydrothermal etching reaction to obtain an intermediate product;
[0012] The intermediate product is mixed with a cobalt-based compound and then calcined to obtain the single-atom Co-anchored TiO2 catalyst.
[0013] Preferably, the dicarboxylic acid comprises terephthalic acid or 2-aminoterephthalic acid;
[0014] The organic titanium is tetrabutyl titanate or tetraisopropyl titanate;
[0015] The cobalt-based compound is cobalt nitrate, cobalt chloride or cobalt acetate.
[0016] Preferably, the mass ratio of the dicarboxylic acid to the organic titanium is 2-5:1-3;
[0017] The reaction temperature of the thermal reaction is 120-180° C., and the reaction time is 12-24 hours.
[0018] Preferably, the mass ratio of the MIL-125 precursor to tannic acid is 1:0.5-3;
[0019] The temperature of the hydrothermal etching reaction is 100-200° C., and the reaction time is 1-4 hours.
[0020] Preferably, the mass ratio of the intermediate product to the cobalt-based compound is 500-1000:5-50;
[0021] The calcination temperature is 400-800° C., and the calcination time is 2-4 hours.
[0022] The present invention also provides the use of the single-atom Co-anchored TiO2 catalyst described in the above technical solution or the single-atom Co-anchored TiO2 catalyst prepared by the preparation method in removing organic pollutants in water.
[0023] Preferably, the organic pollutant comprises a plasticizer.
[0024] Preferably, the single-atom Co-anchored TiO2 catalyst is used to remove organic pollutants in water, comprising the following steps:
[0025] The single-atom Co-anchored TiO2 catalyst, peroxysulfate and wastewater to be treated were mixed and phototreated under visible light.
[0026] Preferably, the peroxysulfate comprises one or more of potassium persulfate, potassium peroxymonosulfate, potassium peroxydisulfate, sodium persulfate and sodium peroxymonosulfate;
[0027] The single-atom Co-anchored TiO2 catalyst is used in an amount of 0.2 to 2 g / L;
[0028] The dosage of the persulfate is 0.3-3 g / L;
[0029] The pH value of the wastewater to be treated is 3-12.
[0030] The present invention provides a single-atom Co-anchored TiO2 catalyst, comprising nano-TiO2 and single-atom Co; the single-atom Co is dispersed on the surface of the nano-TiO2; the loading amount of the single-atom Co is 0.1-1wt%, and the rest is nano-TiO2; the nano-TiO2 is donut-shaped, with an outer diameter of 500-700nm, an inner diameter of 50-300nm, and a thickness along the normal direction of the nano-TiO2 of 300-400nm; the specific surface area of the nano-TiO2 is 100-150m 2 / g.
[0031] The single-atom Co-anchored TiO2 catalyst provided by the present invention has a high single-atom loading. The Co single atom enhances the responsiveness of TiO2 to visible light and serves as an activation reaction point for peroxysulfate. 25 Nano titanium dioxide, the catalyst has more active sites, and the specific surface area of the catalyst is larger. The catalyst provided by the present invention has higher visible light activity, which can significantly improve the removal rate of persistent organic pollutants such as plasticizers. The single-atom Co-anchored TiO2 catalyst provided by the present invention can catalyze the degradation of organic pollutants in water bodies with a pH value of 3 to 12, and has good anti-interference properties for anions in the water body. In addition, the catalyst provided by the present invention has excellent reusability, which greatly reduces the economic cost of the catalyst.
[0032] The results of the embodiments and application examples show that the Co loading of the single-atom Co-anchored TiO2 catalyst provided by the present invention is 0.1-1wt%, the DBP degradation rate is 100%, and the specific surface area is 100-150m 2 / g; In the repeated DBP degradation test of Application Example 3 of the present invention, the leaching concentration of Co of the single-atom Co-anchored TiO2 catalyst was less than 0.2 mg / L when it was reused for the third time, and the leaching concentration of Co was less than 0.1 mg / L when it was reused for the 4th to 8th time. The leaching concentration of Co was stable at a low level, indicating that the loss of Co was very small, and after being reused for 8 times, the degradation rate of DBP by the single-atom Co-anchored TiO2 catalyst still reached 96.061%, which has a high catalytic degradation efficiency.
[0033] The present invention also provides a method for preparing the single-atom Co-anchored TiO2 catalyst, comprising the following preparation steps: mixing a dicarboxylic acid with an organic titanium, performing a thermal reaction, and obtaining a MIL-125 precursor; mixing the MIL-125 precursor with tannic acid, performing a hydrothermal etching reaction, and obtaining an intermediate product; and mixing the intermediate product with a cobalt-based compound and calcining the mixture to obtain the single-atom Co-anchored TiO2 catalyst.
[0034] The present invention thermally reacts a dicarboxylic acid with organic titanium to prepare a MIL-125 precursor having a very large specific surface area, which maximizes the attachment sites of Co single atoms on the TiO2 surface. The present invention uses tannic acid to hydrothermally etch the MIL-125 precursor, and oxidatively converts the MIL-125 precursor into erythrocyte-type TiO2, that is, the intermediate product - erythrocyte-type TiO2, so that the TiO2 structure is more stable and prevents excessive collapse into fragments during subsequent calcination. The present invention replaces Ti-O coordination with Co-O coordination to achieve a high dispersion load of Co single atoms on the TiO2 surface, and maximizes the exposure sites of Co single atoms and nanoparticles on TiO2. After calcination, the central area of the erythrocyte-type TiO2 collapses, and eventually forms a shape similar to a donut (such as Figure 1 The preparation method provided by the present invention is mild and simple, and the prepared TiO2 has a high specific surface area and can stably load a large number of Co single atoms, and can be repeatedly recycled and used for many times and still has an excellent degradation effect of organic pollutants. The preparation method provided by the present invention has simple steps, does not need to add a variety of additives, has low cost, is easy to carry out industrial production, and has considerable market application prospects.
[0035] The present invention also provides the use of the single-atom Co-anchored TiO2 catalyst described in the above technical solution in removing organic pollutants from water. The single-atom Co-anchored TiO2 catalyst provided by the present invention and peroxysulfate can 100% degrade phthalates in water under the action of visible light. The single-atom Co-anchored TiO2 catalyst provided by the present invention can catalyze the degradation of organic pollutants in water with a pH value of 3 to 12, and can be used in various scenarios such as natural water bodies, domestic sewage or industrial sewage. After the catalyst provided by the present invention is reused 8 times, the degradation efficiency of phthalates for plasticizers remains at 96.061%, which greatly reduces the cost of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a synthesis flow chart of the single-atom Co-anchored TiO2 catalyst of Example 1;
[0037] Figure 2 This is a SEM image of the MIL-125 precursor prepared in Example 1;
[0038] Figure 3 TEM image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0039] Figure 4 This is the HAADF-STEM image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0040] Figure 5 This is a line scan result diagram of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0041] Figure 6 This is the internal strain diagram of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0042] Figure 7 This is the XRD pattern of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0043] Figure 8 FT-IR image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0044] Fig. 9 This is the XPS graph of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0045] Fig.10 This is the XANES image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0046] Fig.11This is the EXAFS graph of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0047] Fig.12 This is a two-dimensional color block image of the EXAFS of the single-atom Co-anchored TiO2 catalyst prepared in Example 1;
[0048] Fig.13 It is a line graph of the degradation rate of DBP under different pH conditions in Application Example 2;
[0049] Fig.14 It is a bar graph of the DBP degradation rate under the condition of repeated use of the catalyst in Application Example 3;
[0050] Fig.15 It is a line graph of the degradation rate of DBP under different anion conditions of Comparative Example 3;
[0051] Fig.16 It is a line graph of the DBP degradation rates of Application Example 1 and Comparative Application Examples 1-5. DETAILED DESCRIPTION
[0052] The present invention provides a single-atom Co-anchored TiO2 catalyst, comprising nano-TiO2 and single-atom Co;
[0053] The single atomic Co is dispersed on the surface of the nano-TiO2;
[0054] The loading amount of the single-atom Co is 0.1-1wt%, and the rest is nano-TiO2;
[0055] The nano-TiO2 is donut-shaped, with an outer diameter of 500-700nm, an inner diameter of 50-300nm, and a thickness along the normal direction of the nano-TiO2 of 300-400nm; the specific surface area of the nano-TiO2 is 100-150m 2 / g.
[0056] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0057] The single-atom Co anchored TiO2 catalyst provided by the present invention comprises a component single-atom Co with a mass percentage of 0.1 to 1 wt%, more preferably 0.3 to 0.6 wt%. In the present invention, the single-atom Co is dispersed on the surface of TiO2. The present invention uses the single-atom Co to enhance the responsiveness of TiO2 to visible light, and at the same time, serves as an activation reaction point for peroxysulfate, so that the catalyst has more active sites, thereby improving the visible light activity of the catalyst and the degradation efficiency of organic pollutants.
[0058] The single-atom Co-anchored TiO2 catalyst provided by the present invention comprises a residual amount of nano-TiO2. In the present invention, the nano-TiO2 is donut-shaped, with an outer diameter of 500-700nm, preferably 500-600nm, an inner diameter of 50-300nm, preferably 50-200nm, and a thickness along the normal direction of the nano-TiO2 of 300-400nm. In the present invention, the specific surface area of the nano-TiO2 is 100-150m 2 / g.
[0059] The donut-shaped TiO2 provided by the present invention is better than the commercially available P 25 Nano-TiO2 has a larger specific surface area and can stably load more Co single atoms. The nano-TiO2 provided by the present invention has higher visible light activity, can significantly improve the removal rate of persistent organic pollutants such as plasticizers, and can still have excellent degradation effects on organic pollutants after repeated use.
[0060] The present invention also provides a method for preparing the single-atom Co-anchored TiO2 catalyst described in the above technical solution, comprising the following preparation steps:
[0061] The dicarboxylic acid is mixed with the organic titanium and subjected to a thermal reaction to obtain a MIL-125 precursor;
[0062] The MIL-125 precursor is mixed with tannic acid, and subjected to a hydrothermal etching reaction to obtain an intermediate product;
[0063] The intermediate product is mixed with a cobalt-based compound and then calcined to obtain the single-atom Co-anchored TiO2 catalyst.
[0064] The invention mixes dicarboxylic acid with organic titanium and performs thermal reaction to obtain a MIL-125 precursor.
[0065] In the present invention, the dicarboxylic acid preferably includes terephthalic acid or 2-aminoterephthalic acid, more preferably terephthalic acid. In the present invention, the organic titanium is preferably tetrabutyl titanate or tetraisopropyl titanate, more preferably tetrabutyl titanate. In the present invention, the mass ratio of the dicarboxylic acid to the organic titanium is preferably 2-5:1-3, more preferably 3-3.5:1.5-1.6.
[0066] In the present invention, the dicarboxylic acid is preferably prepared into a dicarboxylic acid solution. In the present invention, the solvent of the dicarboxylic acid solution is preferably N,N-dimethylformamide (DMF). In the present invention, the amount ratio of the dicarboxylic acid to DMF is preferably 2-5g:40-100mL. In the present invention, the dicarboxylic acid and DMF are preferably stirred and mixed, and the stirring time is preferably ≥30min.
[0067] In the present invention, the organic titanium is preferably prepared into an organic titanium solution for use. In the present invention, the solvent of the organic titanium solution is preferably a small molecule organic alcohol, more preferably methanol, ethanol or propylene glycol. In the present invention, the volume ratio of the organic titanium to the small molecule organic alcohol is preferably 1 to 3:5 to 20. In the present invention, the organic titanium and the small molecule organic alcohol are preferably stirred and mixed, and the stirring time is preferably ≥30 minutes.
[0068] In the present invention, the thermal reaction is preferably carried out in a reactor. In the present invention, the reaction temperature of the thermal reaction is preferably 120 to 180° C., more preferably 150 to 160° C. In the present invention, the thermal reaction time is preferably 12 to 24 hours, more preferably 18 to 24 hours, and further preferably 24 hours.
[0069] In a specific embodiment of the present invention, it is preferred that the organic titanium solution is quickly added to the dicarboxylic acid solution, and after stirring for 10 minutes, the obtained mixed solution is transferred to a reaction kettle for thermal reaction.
[0070] After the thermal reaction, the present invention preferably further comprises centrifuging the obtained liquid to collect the white product; washing, drying and grinding the white product to obtain the MIL-125 precursor. In the present invention, the washing preferably uses DMF and methanol to wash the obtained white product respectively, the washing times of DMF is ≥3 times, and the washing times of methanol is ≥3 times. In the present invention, the drying is preferably carried out in an oven. In the present invention, the drying temperature is preferably 60°C, and the drying time is preferably 12 hours. In the present invention, the mesh number of the grinding is preferably ≥200 mesh.
[0071] After obtaining the MIL-125 precursor, the present invention mixes the MIL-125 precursor with tannic acid and performs a hydrothermal etching reaction to obtain an intermediate product.
[0072] In the present invention, the mass ratio of the MIL-125 precursor to tannic acid is preferably 1:0.5-3, more preferably 1:1-1.2. In the present invention, the MIL-125 precursor is preferably formulated into a MIL-125 precursor dispersion for use. In the present invention, the amount ratio of the MIL-125 precursor to water in the MIL-125 precursor dispersion is preferably 1g:40-100mL. In the present invention, the water is preferably deionized water. In the present invention, the mixing is preferably carried out under stirring conditions, and the stirring time is preferably 20-40min. In the present invention, after the mixing, the mixed liquid containing the MIL-125 precursor and tannic acid is preferably moved into a reactor for hydrothermal etching reaction. In the present invention, the reactor is preferably a polytetrafluoroethylene reactor.
[0073] In the present invention, the reaction temperature of the hydrothermal etching reaction is preferably 100-200° C., more preferably 120-180° C. In the present invention, the reaction time of the hydrothermal etching reaction is preferably 1-4 hours, more preferably 2-2.5 hours.
[0074] After the hydrothermal etching, the present invention preferably further comprises centrifuging the liquid after the hydrothermal etching reaction, collecting the brown substance, and washing and drying the brown substance. In the present invention, the washing reagent is preferably deionized water, and the number of washings is preferably ≥3 times. In the present invention, the drying temperature is preferably 60°C, and the drying time is preferably 12h.
[0075] In the present invention, the intermediate product is erythrocyte-type TiO2, which has a higher specific surface area and is etched and pre-oxidized to prevent collapse during the subsequent calcination process.
[0076] After obtaining the intermediate product, the present invention mixes the intermediate product with a cobalt-based compound and then calcines the mixture to obtain the single-atom Co-anchored TiO2 catalyst.
[0077] In the present invention, the cobalt-based compound is preferably cobalt nitrate, cobalt chloride or cobalt acetate, more preferably cobalt nitrate.
[0078] In the present invention, the mass ratio of the intermediate product to the cobalt-based compound is preferably 500-1000:5-50, more preferably 500-1000:10-20.
[0079] In the present invention, the intermediate product is preferably prepared into an intermediate product dispersion for use. In the present invention, in the intermediate product dispersion, the ratio of the intermediate product to water is preferably 0.5g:40-100mL. In the present invention, the water is preferably deionized water. In the present invention, the cobalt-based compound is preferably added to the intermediate product aqueous dispersion, and stirred continuously to obtain a mixed solution. In the present invention, the stirring time is preferably ≥4h.
[0080] After the centrifugation, the present invention preferably further comprises washing the precipitate collected after the centrifugation. In the present invention, the washing is preferably washing with deionized water, and the number of washings is preferably ≥ 3 times. In the present invention, the precipitate after washing is preferably calcined.
[0081] In the present invention, the calcination is preferably carried out in air. In the present invention, the heating rate to the calcination temperature is preferably 1-2°C / min. In the present invention, the calcination temperature is preferably 400-800°C, more preferably 400-600°C; the calcination time is preferably 2-4h, more preferably 2-3h.
[0082] Figure 1The synthesis flow chart of the single-atom Co-anchored TiO2 catalyst of Example 1: The present invention mixes a dicarboxylic acid with an organic titanium, performs a thermal reaction, and obtains a MIL-125 precursor. It can be seen that the obtained MIL-125 precursor has a regular and uniform cake-like morphology. The MIL-125 precursor is mixed with tannic acid and subjected to a hydrothermal etching reaction. When the MIL-125 precursor is hydrothermally etched with tannic acid, the hydrothermal etching process first starts from the inner center of the MIL-125 precursor and then collapses on the outside. The intermediate product finally obtained has the shape of a blood cell. This morphology has a larger specific surface area, which helps to adsorb and expose more cobalt single atoms. During the hydrothermal etching reaction, the overall size of the MIL-125 precursor or intermediate product remains substantially unchanged, and the MIL-125 precursor is pre-oxidized and converted into TiO2 during the reaction. Pre-oxidation helps to stabilize the structure of the intermediate product and prevents excessive collapse into fragments during the subsequent calcination process. The intermediate product of erythrocyte-type TiO2 is mixed with a cobalt-based compound. After calcination, the central area collapses further, eventually forming a donut-like shape, with single cobalt atoms dispersed on the surface of nano-TiO2.
[0083] The present invention also provides the use of the single-atom Co-anchored TiO2 catalyst described in the above technical solution or the single-atom Co-anchored TiO2 catalyst prepared by the preparation method in removing organic pollutants in water.
[0084] In the present invention, the organic pollutant preferably includes a plasticizer. In the present invention, the plasticizer is preferably a phthalate plasticizer, and more preferably dibutyl phthalate.
[0085] In the present invention, the specific application of the single-atom Co-anchored TiO2 catalyst in removing organic pollutants from water comprises the following steps:
[0086] The single-atom Co-anchored TiO2 catalyst, peroxysulfate and wastewater to be treated were mixed and phototreated under visible light.
[0087] In the present invention, the light source of the light treatment is preferably a xenon lamp, and the output current is preferably 50-80A.
[0088] In the present invention, the peroxysulfate preferably includes one or more of potassium persulfate, potassium peroxymonosulfate, potassium peroxydisulfate, sodium persulfate and sodium peroxymonosulfate. In the present invention, the peroxysulfate more preferably includes one or more of potassium peroxymonosulfate and potassium persulfate.
[0089] In the present invention, the dosage of the single-atom Co-anchored TiO2 catalyst is preferably 0.2-2 g / L, more preferably 0.4-0.5 g. In the present invention, the dosage of the peroxysulfate is preferably 0.3-3 g / L, more preferably 0.5-1 g / L.
[0090] In the present invention, the pH value of the wastewater to be treated is preferably 3-12, more preferably 4-10.
[0091] The technical solution of the present invention is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0092] Example 1
[0093] (1) Dissolve 3 g of terephthalic acid in 54 mL of DMF and stir for 30 min to obtain a terephthalic acid solution;
[0094] (2) dissolving 1.56 mL of tetrabutyl titanate in 6 mL of methanol and stirring for 30 min to obtain a tetrabutyl titanate methanol solution;
[0095] (3) The obtained tetrabutyl titanate methanol solution was quickly added to the terephthalic acid solution, and after stirring for 10 minutes, the obtained mixed solution was transferred to a polytetrafluoroethylene reactor for thermal reaction at a temperature of 150° C. for 24 hours;
[0096] (4) The feed liquid after the thermal reaction was centrifuged to collect the white product, and the white product was washed with DMF three times, and then washed with methanol three times, and the white product was dried in an oven at 60° C. for 12 h, and then ground under 200 mesh and collected to obtain MIL-125 precursor (i.e. Figure 8 MIL-125 in
[0097] (5) dispersing 1 g of the obtained MIL-125 precursor in 50 mL of deionized water to obtain a MIL-125 precursor dispersion; adding 1 g of tannic acid to the MIL-125 precursor dispersion, stirring for 20 min, and then transferring the mixed dispersion to a polytetrafluoroethylene reactor for a hydrothermal etching reaction at a temperature of 150° C. for 2 h;
[0098] (6) The feed solution after the hydrothermal etching reaction was centrifuged to collect the brown product, and the brown substance was washed with deionized water three times, and the brown substance was dried in an oven at 60° C. for 12 h, and then ground and collected to obtain an intermediate product (i.e. Figure 8 E-TiO2 in
[0099] (7) 500 mg of the intermediate product was dispersed in 50 mL of deionized water, 20 mg of cobalt nitrate was added, and the mixture was stirred for 4 h. The mixture was centrifuged and the precipitate (i.e. Figure 8 The Co-E-TiO2 in the sample was washed with deionized water for 3 times;
[0100] (8) The obtained precipitate was transferred to a crucible and calcined in air. The temperature was raised to 400°C at a heating rate of 1°C / min and maintained for 2 h to obtain a single-atom Co-anchored TiO2 catalyst (i.e. Figure 8 Co SA -TiO2).
[0101] Figure 2 This is the SEM image of the MIL-125 precursor prepared in Example 1. Figure 2 It can be seen that the MIL-125 precursor has a regular and uniform cake-like morphology with a diameter of 500-700nm and a thickness of 300-400nm.
[0102] Figure 3 TEM image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Figure 3 It can be seen that the morphology of the obtained single-atom Co-anchored TiO2 catalyst is donut-shaped, with an outer diameter of 500-700nm, an inner diameter of 50-300nm, and a thickness along the normal direction of nano-TiO2 of 300-400nm.
[0103] Figure 4 This is the HAADF-STEM image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Figure 4 Figure a is the HAADF-STEM image of STEM high-angle annular dark field HAADF mode imaging. Figure 4 As can be seen in Figure a: clear and bright contrast points can be seen on the Ti atomic array ( Figure 4 This is due to the fact that Co atoms have a larger atomic mass than Ti atoms, so they appear larger and brighter. Figure 4 Figure b is the fitted HAADF-STEM image, which has a more intuitive comparison effect compared to Figure a. Figure 4 In Figure c, the purple base is Ti atoms, while the red parts are clearer and brighter contrast points, which are Co atoms.
[0104] Figure 5 This is a line scan result of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Figure 5It can be seen that the results of the linear scan show both Ti and Co atoms, and Co has a stronger signal. At the same time, the catalyst contains a large number of defects, which is conducive to the subsequent separation of hole-electron pairs.
[0105] Figure 6 This is the internal strain diagram of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Figure 6 Figure a is the HAADF-STEM image of the single-atom Co-anchored TiO2 catalyst. Figure 6 Figure b is calculated using Geometric Phase Analysis (GPA) Figure 6 From the analysis of the internal strain in Figure a, it can be seen that: Figure 6 The shear component (ε xy ), and geometric phase analysis (GPA) is used to calculate the corresponding strain distribution of Co SA -HAADF-STEM images of TiO2 show the internal strain of selected areas to better illustrate the strain on the catalyst surface. The lattice changes provide a quantitative assessment of the compressive strain at specific locations on the surface-modified single-atom Co-anchored TiO2 catalyst, which is further illustrated by the corresponding strain distribution. Figure 6 The huge internal strain can be clearly observed in Figure b. Figure 6 A clear blue patch appears in the upper part of the b-image, corresponding to the negative strain position, indicating the various strains on the site. The red area in the lower part indicates that there is obvious stretching at this position. The unsaturation of the Co site is further aggravated due to the change of the electronic structure by strain engineering.
[0106] Figure 7 The XRD pattern of the single-atom Co-anchored TiO2 catalyst prepared in Example 1 is shown in FIG. Figure 7 It can be seen that the diffraction peaks of the synthesized MIL-125 are consistent with the characteristic peaks of typical MIL-125, indicating that the MIL-125 precursor was successfully synthesized. SA -TiO2 samples, the peaks at 25.3°, 37.8°, 48.0°, 55.1° and 52.7° correspond to the (101), (004), (200), (211) and (204) crystal planes of TiO2, respectively, which is consistent with JCPDS: 21-1272. There is no Co signal in the XRD spectrum, indicating that there is no Co-composed crystal plane in the single-atom Co-anchored TiO2 catalyst, further proving that Co exists in the catalyst in the form of a single atom.
[0107] Figure 8FT-IR image of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Figure 8 It can be seen that the synthetic erythrocyte-type TiO2 ( Figure 8 The E-TiO2 in the MIL-125 precursor still retains most of the functional groups, and there is no significant difference before and after etching. Figure 8 Co SA -TiO2) at 690cm -1 A broad low-frequency band is shown near it, which is mainly due to the vibrations of Ti-O-Ti and Ti-O.
[0108] Fig. 9 This is the XPS graph of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Fig. 9 The a graph in the figure is the Co2p graph. Fig. 9 As can be seen from Figure a: Co 2+ The energy spectrum peaks appear at 780.2eV and 795.2eV, and its satellite peaks appear at 786.8eV and 802.7eV. Fig. 9 Figure b in the figure is the O1s diagram. Fig. 9 As can be seen in Figure b, the O1s spectrum presents a broad asymmetric peak, which can be deconvoluted into three different peaks at 529.3, 530 and 531.3 eV, corresponding to the lattice oxygen (L O ), vacancy oxygen (V O ) and chemically adsorbed oxygen (C O ). This indicates that the single-atom Co-anchored TiO2 catalyst Co SA -TiO2 has a large amount of V O , which not only leads to an increase in the electron density around the Ti site, but also facilitates the separation of electron-hole pairs during the photocatalytic process because of the presence of defects.
[0109] Fig.10 This is the XANES graph of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Fig.10 It can be seen that the single-atom Co-anchored TiO2 catalyst Co SA The absorption edge of -TiO2 is located between Co foil and CoO, indicating that the single-atom Co-anchored TiO2 catalyst Co SA The valence state of Co atoms in -TiO2 is between 0 and +2. SA The Cok absorption edge position of -TiO2 is closer to CoO than to Co foil, indicating that the single Co atom carries a positive charge and the valence state is close to +2.
[0110] Fig.11This is the EXAFS graph of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Fig.11 It can be seen that the coordination environment of Co sites in different Co compounds changes. There is an obvious peak at 1.8 and 2.5, which is due to the effect of Co-Co bond. There are two peaks at , which are related to Co-O and Co-Co coordination, respectively. SA The TiO2 spectrum shows only Co-O bonds but no Co-Co bonds, indicating that there are no Co or CoO clusters / particles, which further confirms the atomic dispersion of Co.
[0111] Fig.12 This is a two-dimensional color block diagram of the EXAFS spectrum of the single-atom Co-anchored TiO2 catalyst prepared in Example 1. Fig.12 Figure a is a two-dimensional color block diagram of Co foil, Figure b is a two-dimensional color block diagram of CoO, and Figure c is a two-dimensional color block diagram of single-atom Co-anchored TiO2 catalyst. By comparison, it can be seen from the figure that compared with the reference contour map of Co foil and CoO after wavelet transformation, it is found that the single-atom Co-anchored TiO2 catalyst Co SA The absence of Co-Co coordination peaks in TiO2 confirms that the Co species are strictly separated, thus demonstrating the Co-Co-free performance of the single-atom Co-anchored TiO2 catalyst. SA -Co in TiO2 exists in the form of single atoms.
[0112] Example 2
[0113] (1) 3.27 g of 2-aminoterephthalic acid was dissolved in 54 mL of DMF and stirred for 30 min to obtain a 2-aminoterephthalic acid solution;
[0114] (2) dissolving 1.56 mL of tetrabutyl titanate in 6 mL of methanol and stirring for 30 min to obtain a tetrabutyl titanate methanol solution;
[0115] (3) The obtained tetrabutyl titanate methanol solution was quickly added to the 2-aminoterephthalic acid solution, and after stirring for 10 minutes, the obtained mixed solution was transferred to a polytetrafluoroethylene reactor for thermal reaction at a temperature of 120° C. for 24 hours;
[0116] (4) centrifuging the liquid after the thermal reaction, collecting the white product, washing the obtained white product 3 times with DMF, and then washing the obtained white product 3 times with methanol, drying the white product in an oven at 60° C. for 12 h, grinding it at 200 mesh, and collecting it to obtain a MIL-125 precursor;
[0117] (5) dispersing 1 g of the obtained MIL-125 precursor in 50 mL of deionized water to obtain a MIL-125 precursor dispersion; adding 1.2 g of tannic acid to the MIL-125 precursor dispersion, stirring for 20 min, and then transferring the mixed dispersion to a polytetrafluoroethylene reactor for a hydrothermal etching reaction at a temperature of 120° C. for 2 h;
[0118] (6) centrifuging the feed solution after the hydrothermal etching reaction, collecting the brown product, washing the obtained brown substance with deionized water three times, drying the brown substance in an oven at 60° C. for 12 h, grinding and collecting to obtain an intermediate product;
[0119] (7) 500 mg of the obtained intermediate product was dispersed in 50 mL of deionized water, 30 mg of cobalt nitrate was added, and the mixture was stirred for 4 h. The mixture was centrifuged to collect the precipitate, and the precipitate was washed with deionized water 3 times;
[0120] (8) The obtained precipitate was transferred to a crucible and calcined in air at a heating rate of 1°C / min to a calcination temperature of 600°C and maintained for 2 hours. After cooling to room temperature, a single-atom Co-anchored TiO2 catalyst was obtained.
[0121] Example 3
[0122] (1) Dissolve 3 g of terephthalic acid in 54 mL of DMF and stir for 30 min to obtain a terephthalic acid solution;
[0123] (2) dissolving 1.25 mL of tetraisopropyl titanate in 6 mL of methanol and stirring for 30 min to obtain a tetraisopropyl titanate methanol solution;
[0124] (3) The obtained tetraisopropyl titanate methanol solution was quickly added to the terephthalic acid solution, and after stirring for 10 minutes, the obtained mixed solution was transferred to a polytetrafluoroethylene reactor for thermal reaction at a temperature of 180° C. for 24 hours;
[0125] (4) centrifuging the liquid after the thermal reaction, collecting the white product, washing the obtained white product 3 times with DMF, and then washing the obtained white product 3 times with methanol, drying the white product in an oven at 60° C. for 12 h, grinding it at 200 mesh, and collecting it to obtain a MIL-125 precursor;
[0126] (5) dispersing 1 g of the obtained MIL-125 precursor in 50 mL of deionized water to obtain a MIL-125 precursor dispersion; adding 1.2 g of tannic acid to the MIL-125 precursor dispersion, stirring for 20 min, and then transferring the mixed dispersion to a polytetrafluoroethylene reactor for a hydrothermal etching reaction at a temperature of 180° C. for 2 h;
[0127] (6) centrifuging the feed solution after the hydrothermal etching reaction, collecting the brown product, washing the obtained brown substance with deionized water three times, drying the brown substance in an oven at 60° C. for 12 h, grinding and collecting to obtain an intermediate product;
[0128] (7) 500 mg of the obtained intermediate product was dispersed in 50 mL of deionized water, 20 mg of cobalt chloride was added, and the mixture was stirred for 4 h. The mixture was centrifuged to collect the precipitate, and the precipitate was washed with deionized water 3 times;
[0129] (8) The obtained precipitate was transferred to a crucible and calcined in air at a heating rate of 1°C / min to a calcination temperature of 600°C and maintained for 2 hours. After cooling to room temperature, a single-atom Co-anchored TiO2 catalyst was obtained.
[0130] Example 4
[0131] (1) 3.27 g of 2-aminoterephthalic acid was dissolved in 54 mL of DMF and stirred for 30 min to obtain a 2-aminoterephthalic acid solution;
[0132] (2) dissolving 1.25 mL of tetraisopropyl titanate in 6 mL of methanol and stirring for 30 min to obtain a tetraisopropyl titanate methanol solution;
[0133] (3) The obtained tetraisopropyl titanate methanol solution was quickly added to the 2-aminoterephthalic acid solution, and after stirring for 10 minutes, the obtained mixed solution was transferred to a polytetrafluoroethylene reactor for thermal reaction at a temperature of 150° C. for 18 hours;
[0134] (4) centrifuging the liquid after the thermal reaction, collecting the white product, washing the obtained white product 3 times with DMF, and then washing the obtained white product 3 times with methanol, drying the white product in an oven at 60° C. for 12 h, grinding it at 200 mesh, and collecting it to obtain a MIL-125 precursor;
[0135] (5) dispersing 1 g of the obtained MIL-125 precursor in 50 mL of deionized water to obtain a MIL-125 precursor dispersion; adding 1.5 g of tannic acid to the MIL-125 precursor dispersion, stirring for 20 min, and then transferring the mixed dispersion to a polytetrafluoroethylene reactor for a hydrothermal etching reaction at a temperature of 150° C. for 6 h;
[0136] (6) centrifuging the feed solution after the hydrothermal etching reaction, collecting the brown product, washing the obtained brown substance with deionized water three times, drying the brown substance in an oven at 60° C. for 12 h, grinding and collecting to obtain an intermediate product;
[0137] (7) 500 mg of the obtained intermediate product was dispersed in 50 mL of deionized water, 20 mg of cobalt acetate was added, and the mixture was stirred for 4 h. The mixture was centrifuged to collect the precipitate, and the precipitate was washed with deionized water 3 times;
[0138] (8) The obtained precipitate was transferred to a crucible and calcined in air at a heating rate of 1°C / min to a calcination temperature of 400°C and maintained for 4 hours. After cooling to room temperature, a single-atom Co-anchored TiO2 catalyst was obtained.
[0139] Comparative Example 1
[0140] The difference from Example 1 is that tannic acid is not added and hydrothermal etching reaction is not performed.
[0141] (1) Dissolve 3 g of terephthalic acid in 54 mL of DMF and stir for 30 min to obtain a terephthalic acid solution;
[0142] (2) dissolving 1.56 mL of tetrabutyl titanate in 6 mL of methanol and stirring for 30 min to obtain a tetrabutyl titanate methanol solution;
[0143] (3) The obtained tetrabutyl titanate methanol solution was quickly added to the terephthalic acid solution, and after stirring for 10 minutes, the obtained mixed solution was transferred to a polytetrafluoroethylene reactor for thermal reaction at a temperature of 150° C. for 24 hours;
[0144] (4) centrifuging the liquid after the thermal reaction, collecting the white product, washing the obtained white product 3 times with DMF, and then washing the obtained white product 3 times with methanol, drying the white product in an oven at 60° C. for 12 h, grinding it at 200 mesh, and collecting it to obtain a MIL-125 precursor;
[0145] (5) Disperse 1 g of the obtained MIL-125 in 50 mL of deionized water, add 20 mg of cobalt nitrate, continue stirring for 4 h, centrifuge the mixture, collect the precipitate, and wash the precipitate with deionized water three times;
[0146] (6) The obtained precipitate was transferred to a crucible and calcined in air at a heating rate of 1°C / min to a calcination temperature of 400°C and maintained for 2 hours to obtain a single-atom Co-anchored TiO2 catalyst.
[0147] Application Example 1
[0148] 10 mg of dibutyl phthalate (DBP) and 50 mL of deionized water were added to a beaker to simulate wastewater, the pH value of the simulated wastewater was 5.71, and then 20 mg of the catalyst obtained in Example 1 was added. The mixture was placed in a dark environment and adsorbed for 30 minutes under continuous stirring. Then, 25 mg of potassium peroxymonosulfate (PMS) was added and stirred continuously to obtain a reaction solution.
[0149] Turn on the xenon lamp light source (equipment type: Microsolar 300) with a filter (UVCUT 400), and treat the beaker containing the reaction solution under visible light for 30 minutes.
[0150] Add 2 mg Na2S2O3·5H2O to a 2 mL glass centrifuge tube to quench free radicals and terminate the reaction; take 1 mL of the reaction solution and add it to the centrifuge tube every 5 min, and place the centrifuge tube in a shaking stirrer and stir for 10 s.
[0151] The glass centrifuge tube was centrifuged at a speed of 2500 r / min to obtain a supernatant and a lower solution.
[0152] Test of DBP degradation rate: The supernatant was taken into a brown sample bottle, and the DBP content in the reaction solution was detected by high performance liquid chromatography and standard sample-linear regression method. The DBP degradation rates of the single-atom Co-anchored TiO2 catalysts obtained in Examples 1 to 4 and Comparative Example 1 were respectively detected. The test results are shown in Table 1.
[0153] Co ion leaching concentration test: Take 20 mL of the reaction solution after visible light treatment for 30 minutes, and use inductively coupled plasma optical emission spectrometer (ICP) to detect the concentration of Co ions leached into the reaction solution. According to Application Example 1, the Co ion leaching concentration of the single-atom Co-anchored TiO2 catalyst leached into the reaction solution obtained in the embodiment and the comparative example was verified respectively, and the test results are shown in Table 1.
[0154] Co loading test: Take 20 mg of the single-atom Co-anchored TiO2 catalyst obtained in the embodiment and the comparative example in a beaker, add 5 mL of aqua regia for digestion, and add deionized water to dilute to 50 mL after digestion; take 20 mL of the diluted digestion solution, and use an inductively coupled plasma optical emission spectrometer (ICP) to detect the concentration of the leached Co ions. After calculation, the Co loading on the single-atom Co-anchored TiO2 catalyst is obtained. The test results are shown in Table 1.
[0155] Specific surface area test: Take 100 mg of the single-atom Co-anchored TiO2 catalyst obtained in the embodiment and the comparative example, and use a fully automatic surface area and pore size distribution analyzer to detect the specific surface area. The specific surface area of the single-atom Co-anchored TiO2 catalyst is obtained. The test results are shown in Table 1.
[0156] Table 1 Test results of single-atom Co-anchored TiO2 catalysts obtained in Examples and Comparative Examples
[0157]
[0158] It can be seen from Table 1 that the performance of the single-atom Co-anchored TiO2 catalyst prepared in Example 1 is the best, and the catalyst prepared in Comparative Example 1 without etching is much lower in Co loading and degradation efficiency than Example 1;
[0159] The specific surface area of the single-atom Co-anchored TiO2 catalyst obtained by the present invention is 100 to 150 m 2 / g, while the commercially available P 25 The specific surface area of TiO2 is generally 60m 2 / g.
[0160] Application Example 2
[0161] The difference from Application Example 1 is that the pH values of the simulated wastewater were adjusted to 2, 4, 5.71, 8 and 10 respectively, and samples were taken to detect the Co leaching concentration and the degradation rate of DBP respectively. The test results are shown in Table 2.
[0162] Table 2 Test results under different pH conditions
[0163]
[0164]
[0165] It can be seen from Table 2 that the single-atom Co-anchored TiO2 catalyst Co prepared by the present invention SA -TiO2 has good pH adaptability and has a good degradation effect in a wide range, but under strong acidic conditions, the catalyst performance will deteriorate due to the leaching of Co.
[0166] Fig.13 This is a line chart of the degradation rate of DBP under different pH conditions in Application Example 2, which intuitively shows the degradation effect of different pH conditions on DBP. Fig.13 It can be seen that the pH of the solution is an important factor affecting advanced oxidation and is also one of the main limiting factors in the actual water application process. The DBP degradation effect in the pH range of 2 to 10 was analyzed: under weakly acidic conditions (pH = 4), the degradation efficiency decreased slightly, and the reaction rate was 0.1207min -1 However, under extremely acidic conditions (pH = 2), the reaction was significantly inhibited, which may be due to the shedding of Co anchored on the catalyst. + The ions will form strong hydrogen bonds with the peroxy (-OO-) bonds in potassium peroxymonosulfate PMS, thereby minimizing the generation of reactive free radicals in the medium. At lower pH values, the parent acid H2SO5 will replace HSO5 - Peroxymonosulfate becomes the main substance and also interferes with Co 2+ To Co 3+ Under alkaline conditions (pH = 8, 10), the degradation effect did not change significantly, indicating that the catalyst also has good stability under strong alkaline conditions. In addition, under pH>9.5, HSO5 - Will be converted into SO5 2- , which produces SO4 2- It is more effective than the former. In actual water bodies, extreme pH conditions are usually not achieved. Therefore, the single-atom Co-anchored TiO2 catalyst Co prepared by the present invention SA -TiO2 can be used in most water bodies.
[0167] Application Example 3
[0168] The single-atom Co-anchored TiO2 catalyst obtained in Example 1 was subjected to 8 repeated tests of dibutyl phthalate DBP degradation rate according to Application Example 1: During the first 3 repeated degradation tests, the single-atom Co-anchored TiO2 catalyst after the test was centrifuged and recovered, and then washed with deionized water 3 times and dried, and then it could be reused; the single-atom Co-anchored TiO2 catalyst recovered after the 4th repeated use was washed with deionized water 3 times and placed in a reactor at 400°C, re-calcined for 30 minutes, and then cooled to room temperature and continued to repeat the DBP degradation test. The degradation rate of dibutyl phthalate DBP and the Co leaching concentration of the catalyst used each time were detected, and the test results are shown in Table 3.
[0169] Table 3 Test results of the reused single-atom Co-anchored TiO2 catalyst
[0170]
[0171]
[0172] It can be seen from Table 3 that the single-atom Co-anchored TiO2 catalyst Co prepared by the present invention SA -TiO2 has good cycle performance and can be reused, which is economical.
[0173] Fig.14 The bar chart of DBP degradation rate under the condition of repeated use of catalyst in Application Example 3 is used to intuitively show the degradation effect of DBP in each cycle. Fig.14 It can be seen that the cyclability of the catalyst directly affects the economic applicability in practical applications and can directly reflect the stability of the reaction material. SA -TiO2 can still maintain a DBP degradation efficiency of 96.061% after 8 reuses, which shows the excellent stability of the catalyst. In the first three cycles, the catalyst was simply recycled by washing and drying, which easily led to the active sites being covered by degradation intermediates. Therefore, after the fourth cycle, the single-atom Co-anchored TiO2 catalyst Co SA -TiO2 was cleaned and calcined at 400°C for 30 minutes to restore the catalyst performance. In the repeated DBP degradation test, the Co leaching concentration of the single-atom Co-anchored TiO2 catalyst was less than 0.2 mg / L when it was reused for the third time, and the Co leaching concentration was less than 0.1 mg / L when it was reused for the 4th to 8th time. The Co leaching concentration was stable at a low level, indicating that the loss of Co was very small, and the Co atoms anchored on TiO2 were highly stable. After one cycle, the loss of Co was only about 2%, which proved that the single-atom Co-anchored TiO2 catalyst prepared by the present invention has excellent stability.
[0174] Application Comparative Example 1
[0175] The difference from Application Example 1 is that the single-atom Co-anchored TiO2 catalyst obtained in Example 1 is not added, and visible light is not used.
[0176] The degradation rate of DBP was 10.806%.
[0177] Application Comparative Example 2
[0178] The difference from Application Example 1 is that potassium peroxymonosulfate PMS is not added and visible light is not used.
[0179] The degradation rate of DBP was 0.929%.
[0180] Application Comparative Example 3
[0181] The difference from Application Example 1 is that the single-atom Co-anchored TiO2 catalyst obtained in Example 1 is not added.
[0182] The degradation rate of DBP was 48.058%.
[0183] Application Comparative Example 4
[0184] The difference from Application Example 1 is that potassium peroxymonosulfate PMS is not added.
[0185] The degradation rate of DBP was 12.745%.
[0186] Application Comparative Example 5
[0187] The difference from Application Example 1 is that visible light is not used.
[0188] The degradation rate of DBP was 95.68%.
[0189] Application Comparative Example 6
[0190] The difference from Application Example 1 is that the concentration of Cl2 is controlled at 0.05 mol / L in different glass centrifuge tubes. - 、SO4 2- 、NO3 - and HPO4 2- / H2PO4 - , samples were taken to detect the degradation rate of DBP. The test results are shown in Table 4.
[0191] Table 4 Test results of the effect of different anions on DBP degradation rate
[0192] sample Degradation rate of DBP, % <![CDATA[Cl - ]]> 32.692 <![CDATA[SO4 2- ]]> 100 <![CDATA[NO3 - ]]> 100 <![CDATA[HPO4 2- / H2PO4 - ]]> 100
[0193] It can be seen from Table 4 that: - The presence of SO4 resulted in a degradation rate of only 32.69% for dibutyl phthalate (DBP). 2- 、NO3 - and HPO4 2- / H2PO4 - It has little effect on the degradation rate of DBP.
[0194] Fig.15 The line graph of DBP degradation rate under different anion conditions in Comparative Example 3 is used to intuitively show the degradation effect of different anions on DBP. Fig.15 It can be seen that: the effects of common anions in water on DBP degradation were investigated, Cl - Ions tend to interfere with the generation of free radicals by the single-atom Co-anchored TiO2 catalyst, thereby affecting the degradation efficiency of the organic pollutant dibutyl phthalate (DBP). 2- 、NO3 -and HPO4 2- / H2PO4 - It has little effect on the reaction, SO4 2- Easily affected by halogen ions (such as Cl - ) removes and generates chlorine free radicals. Chlorine free radicals have a low redox potential and can react with organic matter to form insoluble chlorides. - The presence of usually exhibits an inhibitory effect, resulting in a significant decrease in the degradation efficiency of the catalyst.
[0195] Fig.16 The line graph of the DBP degradation rate of Application Example 1 and Application Comparative Examples 1 to 5 intuitively shows the degradation effect of Application Example 1 and Application Comparative Examples 1 to 5 on dibutyl phthalate DBP. Fig.16 It can be seen that the present invention found that the prepared single-atom Co-anchored TiO2 catalyst Co SA -TiO2 adsorption and degradation effect of dibutyl phthalate (DBP). SA After the adsorption process of DBP by TiO2 is stabilized, the degradation rate of DBP in Comparative Example 2 is only 0.929%. In Comparative Example 1, no catalyst is added and no visible light is used, and the degradation rate of DBP is 10.806%. After adding visible light irradiation, the degradation rate of Comparative Example 3 reaches 48.058%. This shows that the single-atom Co-anchored TiO2 catalyst Co prepared by the present invention is SA The synergistic system of TiO2 and peroxymonosulfate PMS significantly increased the degradation effect of dibutyl phthalate DBP, but still could not achieve complete degradation of DBP. In comparative example 5, no visible light was used, and the final degradation rate was 95.68%, indicating that the single-atom Co-anchored TiO2 catalyst Co SA -TiO2 and peroxymonosulfate PMS synergistic system, adding visible light irradiation, photocatalysis and single-atom Co anchored TiO2 catalyst Co SA The combined effect of TiO2 and peroxymonosulfate PMS synergistic system resulted in a final degradation rate of dibutyl phthalate DBP of 100% within 30 minutes.
[0196] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A single-atom Co-anchored TiO2 catalyst, characterized in that: Including nano-TiO2 and single-atom Co; The single atomic Co is dispersed on the surface of the nano-TiO2; The loading amount of the single-atom Co is 0.1-1wt%, and the rest is nano-TiO2; The nano-TiO2 is donut-shaped, with an outer diameter of 500-700nm, an inner diameter of 50-300nm, and a thickness along the normal direction of the nano-TiO2 of 300-400nm; the specific surface area of the nano-TiO2 is 100-150m 2 / g.
2. The method for preparing the single-atom Co-anchored TiO2 catalyst according to claim 1, characterized in that: The method comprises the following preparation steps: The dicarboxylic acid is mixed with the organic titanium and subjected to a thermal reaction to obtain a MIL-125 precursor; The MIL-125 precursor is mixed with tannic acid, and subjected to a hydrothermal etching reaction to obtain an intermediate product; The intermediate product is mixed with a cobalt-based compound and then calcined to obtain the single-atom Co-anchored TiO2 catalyst.
3. The preparation method according to claim 2, characterized in that: The dicarboxylic acid includes terephthalic acid or 2-aminoterephthalic acid; The organic titanium is tetrabutyl titanate or tetraisopropyl titanate; The cobalt-based compound is cobalt nitrate, cobalt chloride or cobalt acetate.
4. The preparation method according to claim 2 or 3, characterized in that: The mass ratio of the dicarboxylic acid to the organic titanium is 2-5:1-3; The reaction temperature of the thermal reaction is 120-180° C., and the reaction time is 12-24 hours.
5. The preparation method according to claim 2, characterized in that: The mass ratio of the MIL-125 precursor to tannic acid is 1:0.5-3; The temperature of the hydrothermal etching reaction is 100-200° C., and the reaction time is 1-4 hours.
6. The preparation method according to claim 2, characterized in that: The mass ratio of the intermediate product to the cobalt-based compound is 500-1000:5-50; The calcination temperature is 400-800° C., and the calcination time is 2-4 hours.
7. Use of the single-atom Co-anchored TiO2 catalyst according to claim 1 or the single-atom Co-anchored TiO2 catalyst prepared by the preparation method according to any one of claims 2 to 6 in removing organic pollutants from water.
8. The use according to claim 7, characterized in that: The organic pollutants include plasticizers.
9. The use according to claim 7, characterized in that: The application method of the single-atom Co-anchored TiO2 catalyst in removing organic pollutants in water comprises the following steps: The single-atom Co-anchored TiO2 catalyst, peroxysulfate and wastewater to be treated were mixed and phototreated under visible light.
10. The use according to claim 9, characterized in that: The peroxysulfate includes one or more of potassium persulfate, potassium peroxymonosulfate, potassium peroxydisulfate, sodium persulfate and sodium peroxymonosulfate; The single-atom Co-anchored TiO2 catalyst is used in an amount of 0.2 to 2 g / L; The dosage of the persulfate is 0.3-3 g / L; The pH value of the wastewater to be treated is 3-12.
Citation Information
Patent Citations
Preparation method and application of TiO2-loaded monatomic Co catalyst
CN109908899A
Doughlet-shaped hollow porous Pt-Ni nanoparticle loaded titanium oxide material and preparation method thereof
CN114377691A
TiO2 photocatalyst with monatomic anchored by metal sites and preparation method of TiO2 photocatalyst
CN114471721A
MOF nano-material and preparation method thereof, and preparation method and application of MOF nano-material loaded with metal monatomic
CN116003821A
Yolk core-shell structured composite material, preparation method of same, and secondary battery containing same
US20230317932A1
